Clock gating techniques using 0.18um CMOS technology / Muhammad Syafiq Ab Rahim - Ab Rahim, Muhammad Syafiq (2011)
This thesis presents a study of clock gating techniques using 0.18um CMOS technology. The objective of this paper is to study the speed of the clock gating technique. Another objective of this paper is to study the power consumption of the clock gating technique. Today’s consumer demands more functionality, energy efficient device and optimized power device. In order to optimize power of a device the simplest control technique is to shut off the clock of the sequential block of the device when there is no function required from that section for some duration. In synchronous digital circuit the clock net is responsible for significant part of power dissipation (up to 40%) [1]. Clock gating is the most common technique used for optimization and improving efficiency but still it leaves one question how efficiently design is clock gated [2].The simulation results are derived using SILVACO EDA tool, the schematic design and simulation are using the Gateway SILVACO EDA tool. The results show that the AND gate clock gating technique give overall better performance with 299.57ps for the propagation delay, 470.19pW power dissipation and average power of 0.002511W.